SPE Latin America and Caribbean Petroleum Engineering Conference 2012
DOI: 10.2118/153602-ms
|View full text |Cite
|
Sign up to set email alerts
|

Unusual Asphaltene Phase Behavior of Fluids from Lake Maracaibo, Venezuela

Abstract: Reservoir fluids from Lake Maracaibo have reportedly caused asphaltene operational problems ranging from plugging of wellbores, pipelines and flowlines to clogging of surface facilities (Garcia et al, 2001). Production of fluids from some part of the region has been dramatically reduced due to asphaltene precipitation and deposition (Vasquez, 2010). Asphaltene and wax precipitation is a serious problem in production, transport and processing of reservoir fluids. Of particular concern are the eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 9 publications
1
16
0
Order By: Relevance
“…The AOP and saturation pressure on the blended sample were found to be 4250 +/-250 psia and 2800 psia. These results were in agreement with the measurements performed in our earlier work (Gonzalez et al, 2012).…”
Section: Asphaltene Onset Measurementssupporting
confidence: 94%
See 2 more Smart Citations
“…The AOP and saturation pressure on the blended sample were found to be 4250 +/-250 psia and 2800 psia. These results were in agreement with the measurements performed in our earlier work (Gonzalez et al, 2012).…”
Section: Asphaltene Onset Measurementssupporting
confidence: 94%
“…Generally the asphaltene onset pressure increases with a decrease in temperature, however, in this case the asphaltene onset pressure decreased with decrease in temperature. The results of the asphaltene precipitation study were reported in our earlier publication (Gonzalez at al, 2012).…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…It is also important to highlight that the amply literature related to thermodynamic models to predict AOPs of petroleum reservoir fluids, included very recent works [187], intrinsically assume the AOPs are true liquid-liquid equilibria. Thus, the approach used in this work is the conventional one followed by hundreds of papers published in the literature (e.g., [114]- [120], [123], [138], [142], [143], [187]).…”
Section: Ill-defined Mixtures: Petroleum Reservoir Fluidsmentioning
confidence: 99%
“…This could explain, in part, the tendency of PC-SAFT to over-predict the onsets of asphaltene precipitation and polymer cloud points at low temperatures [78], [123].…”
mentioning
confidence: 99%